Improving Students’ Vocabulary Achievement Through Short Story at the Eight Grade of SMP Negeri 4 Kendari - Irmawati Irmawati; Titin Rahmiatin; Nur Risky Alfiany (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This study was a classroom action research (CAR) on improving students’ vocabulary achievement through short story to Junior High School. This research was conducted within two cycles in which each cycle consisted of three meetings. Either first cycle or second cycle consisted of planning, action, observation/evaluation, and reflection. The subject of this study was 8th Grade students’ at SMP Negeri 4 Kendari. A number of the students in the class were 32 students. Then, the instruments were used in this study include observation sheet of teacher’s and students’ activity, vocabulary test. The improvement could be seen in the result of students’ achievement after conducting this study was 90.62% proved that it achieved classical achievement. Moreover, percentage of teacher’s and student’s activity also achieved 800% in the second cycle. In other words, the students’ vocabulary at Grade 8th of SMP Negeri 4 Kendari improved through short story.